Tepary bean (Phaseolus acutifolius) lectin fraction provokes reversible adverse effects on rats’ digestive tract - Pita-López, Wendoline (Toxicol Res (Camb), 2020)
The Tepary bean (Phaseolus acutifolius) lectin fraction (TBLF) exhibits differential cytotoxicity on colon cancer cells and inhibition of early tumorigenesis in the colon (50 mg/kg, three times per week, for 6 weeks). TBLF showed low toxicity with the ability to activate the immune system; however, some adverse effects are the loss in body weight gain, intestinal atrophy, and pancreatic hyperplasia. After a recovery period of 2 weeks after treatment, reversion of pancreatic hyperplasia but no recovery of intestinal atrophy was observed. As TBLF has shown anticancer effects on the colon, it is important to characterize the adverse effects and how they can be reversed. Sprague Dawley rats were administered with TBLF (50 mg/kg) for 6 weeks, three times per week, and then allowed to recover for 6 weeks post-treatment. After TBLF administration, small intestine atrophy, villus atrophy, and cryptic hyperplasia were confirmed, as well as increased intestinal mucus production, increased permeability and a decrease in the apparent ileal digestibility of crude proteins. The colon showed damage in the simple prismatic tissue and decreased crypt depth, and changes in microbiota and a decrease in the apparent fecal digestibility of crude protein were determined. Our results show that the adverse effects provoked by TBLF were partially reversed after 6 weeks of recovery post-treatment, suggesting that increasing the recovery period it could be possible to reverse all adverse effects observed.